High-breathability hydrophobic non-woven fabric and production method thereof

By using PTFE micropowder, nanosilica, polyurethane resin, antistatic agent and polyester fiber in nonwoven fabrics, and attaching a hydrophobic treatment layer to the surface, the problem of difficult balance of breathability and waterproofness in traditional nonwoven fabrics under high humidity or extreme climate conditions is solved, and the coexistence of high breathability and waterproof performance is achieved.

CN119571542APending Publication Date: 2025-03-07WUXI HONGQING NON WOVEN FABRIC CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411762939.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional non-woven fabrics are difficult to maintain ideal breathability and waterproofing under high humidity or extreme climate conditions, and the balance between breathability and hydrophobicity is difficult to achieve, affecting the protection effect of the product.

Method used

The filaments are extruded into 10-15% PTFE fine powder, 5-10% nano silica, 3-6% polyurethane resin, 1-3% antistatic agent and residual polyester fibers, and a hydrophobic treatment layer is attached to the surface of the filaments. A highly breathable hydrophobic nonwoven fabric is formed by electrospinning technology and heat setting treatment.

Benefits of technology

It realizes that non-woven fabrics effectively block the invasion of water molecules while maintaining high breathability, improves the waterproof performance and hygiene standards of the product, and enhances the mechanical strength and durability of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571542A_ABST
    Figure CN119571542A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of textiles, in particular to a high-breathability hydrophobic non-woven fabric and a production method thereof.The high-breathability hydrophobic non-woven fabric is prepared from, by mass, 10-15% of PTFE micro powder, 5-10% of nano silicon dioxide, 3-6% of polyurethane resin, 1-3% of antistatic agent and the balance polyester fibers through extrusion, the hydrophobic treatment layers are attached to the surfaces of the filaments; due to the extremely low surface energy and hydrophobic property of the PTFE micro powder, namely polytetrafluoroethylene, the non-woven fabric can keep high air permeability, invasion of water molecules is effectively blocked, and the air-permeable and waterproof effects are achieved; due to the addition of nano silicon dioxide and polyurethane resin, the mechanical strength and durability of the non-woven fabric are remarkably improved; the waterproof performance of the non-woven fabric is further enhanced through the hydrophobic treatment layer, hydrophobic treatment is carried out before the filaments are bonded to prepare the fabric, and the high air permeability and the waterproof performance coexist.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, and in particular to a highly breathable and hydrophobic nonwoven fabric and a production method thereof. Background Art

[0002] In the field of textiles and medical protection, highly breathable and hydrophobic nonwoven fabrics are highly favored due to their unique properties. Although traditional nonwoven fabrics have certain breathability and waterproof properties, in actual applications, especially under high humidity or extreme climatic conditions, sanitary nonwoven fabrics often find it difficult to achieve the desired effect. For example, after long-term use, the hydrophobic properties of conventional nonwoven fabrics will gradually decrease, causing liquid penetration and affecting the protective effect of the product. In addition, the balance between breathability and hydrophobicity is also a major challenge. Excessive hydrophobicity often comes at the expense of breathability, which is particularly evident in protective fabrics or outdoor equipment that need to be worn for a long time.

[0003] In recent years, researchers have been committed to developing new highly breathable and hydrophobic nonwoven fabrics. This type of nonwoven fabric is processed by a special process, which not only maintains a certain degree of breathability, but also reduces the penetration of water molecules, while improving the circulation of air and water vapor, thereby improving the comfort and protective performance of the product. However, the balance between the breathability and hydrophobicity of such products on the market and the production methods are still insufficient. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a highly breathable and hydrophobic nonwoven fabric and a production method thereof.

[0005] The technical scheme of the present invention is: a highly breathable and hydrophobic non-woven fabric, which is composed of 10-15% PTFE powder, 5-10% nano-silicon dioxide, 3-6% polyurethane resin, 1-3% antistatic agent and the rest polyester fiber extruded filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 10-80 mg / m 2 .

[0006] Description: The use of environmentally friendly materials, polyester fiber and specific treatment agents reduces pollution to the environment while ensuring the safety of the product and the comfort of human contact; the hydrophobic treatment layer can prevent liquid penetration, reduce the chance of microbial growth, and improve the hygiene standards of the product.

[0007] The present invention also provides a method for producing the highly breathable and hydrophobic nonwoven fabric, comprising the following steps:

[0008] S1. Raw material mixing

[0009] The polyester fiber, PTFE powder, nano-silicon dioxide, polyurethane resin and antistatic agent are uniformly mixed according to the formula ratio to obtain a mixture;

[0010] S2. Preparation of molten mixture

[0011] The mixed material obtained in S1 is introduced into a melt extruder, and the temperature is controlled to be 220-260° C. to fully melt the PTFE powder to obtain a molten mixture;

[0012] S3, extrusion modification treatment

[0013] The molten mixture obtained in S2 is stretched into filaments through an electrospinning device, the filaments are cooled to room temperature, then immersed in deionized water for cleaning, and after drying, the filaments are completely immersed in a lipase solution and stirred for reaction for 3 to 15 hours; then, they are fully washed with distilled water and dried to obtain modified fibers;

[0014] S4. Preparation of non-woven fabric

[0015] The modified fiber obtained in S3 is immersed in a hydrophobic dispersion, stirred and immersed for 5 to 15 minutes, a hydrophobic treatment layer is attached to the surface of the modified fiber, and then taken out and dried to prepare a non-woven fabric with a microporous structure;

[0016] S5. Finalization

[0017] The non-woven fabric described in S4 is subjected to heat setting treatment, the temperature of the heat setting treatment is controlled to be 180-220° C., and the heat setting time is 20-80 seconds to obtain a highly breathable and hydrophobic non-woven fabric.

[0018] Description: The raw materials are mixed according to a specific formula ratio and melted at a precise temperature of 220-260°C, ensuring that the PTFE micropowder reacts fully to form a uniform molten mixture, which is beneficial to improving the air permeability and hydrophobicity of the non-woven fabric; the molten mixture is stretched into filaments by electrospinning technology, and combined with the impregnation and reaction of the lipase solution, the hydrophilic and oleophobic properties of the fiber and its structural stability are significantly enhanced, ensuring that the fiber maintains a good morphology in subsequent treatment; the modified fiber is immersed in a hydrophobic dispersion, and a hydrophobic layer is formed on the fiber surface through a chemical reaction, further enhancing the waterproof performance of the non-woven fabric while maintaining air permeability; through a heat setting treatment at a specific temperature and time, the non-woven fabric forms a stable microporous structure, and the heat setting treatment is carried out at a temperature of 180-220°C and a time range of 20-80s, which not only ensures the molding effect of the non-woven fabric, but also avoids the degradation of material properties caused by high temperature, ensuring the final quality of the product.

[0019] Furthermore, the antistatic agent described in S1 is antistatic agent ZJ-NW16.

[0020] Description: ZJ-NW16 antistatic agent can effectively reduce the surface resistance of non-woven fabrics and reduce static electricity accumulation. Good antistatic performance can improve safety and comfort. The cooling rate of 3-10℃ helps to quickly stabilize the fiber structure, prevent the fiber from breaking due to uneven shrinkage during the cooling process, and ensure the strength and dimensional stability of the fiber. The stretching ratio of 1.5-2 times can effectively adjust the molecular arrangement of the fiber, increase the ductility and strength of the fiber, and ensure that the fiber will not be structurally damaged due to excessive stretching. Through precisely controlled cooling and stretching treatment, the microporous structure of the fiber is optimized, which not only maintains a high air permeability, but also ensures the effectiveness of the hydrophobic treatment, and improves the comprehensive performance of the non-woven fabric.

[0021] Furthermore, the temperature of the stirring reaction in S3 is controlled at 40-60°C; the cooling rate is 3-10°C, and the stretching ratio is 1.5-2 times.

[0022] Description: Appropriate temperature can accelerate the interaction between lipase and other reactants and improve reaction efficiency, thereby shortening processing time and improving production efficiency; as a protein, the activity of lipase is significantly affected by temperature. The temperature range of 40-60°C is usually the ideal temperature range for many enzymes to maintain high activity, which can ensure that lipase can effectively catalyze the reaction and improve the hydrophilic and oleophobic properties of the fiber; excessively high temperature can cause denaturation and inactivation of biocatalysts such as lipase, and also affect the stability of other raw materials; controlling within the appropriate temperature range can reduce the risk of thermal degradation and maintain the integrity of raw materials and products; by precisely controlling the temperature of the stirring reaction, the depth and uniformity of the fiber surface treatment can be better regulated, thereby obtaining higher quality non-woven products.

[0023] Furthermore, the lipase solution in S3 is composed of 0.1-9% Novozym 435, 3-15% ethylene glycol and the balance water, in terms of mass percentage.

[0024] Description: Lipase Novozym 435 can catalyze a variety of chemical reactions under mild conditions, including esterification, hydrolysis and transesterification; ethylene glycol, as a polyol, can serve as a cofactor for lipase to help regulate the hydrophilicity and solubility of the reaction, thereby affecting the microstructure and surface properties of the fiber; water, as a solvent, ensures the fluidity of the reaction mixture and the expression of enzyme activity; the content of Novozym 435 in the lipase solution has a direct effect on the reaction rate and conversion rate; an appropriate amount of lipase can ensure sufficient catalytic activity, while too high an enzyme concentration will cause the reaction system to be too crowded, affecting the stability and reuse of the enzyme; the addition of ethylene glycol can improve the stability of lipase, especially in organic solvents or non-aqueous phases, which helps maintain the three-dimensional structure of the enzyme and thus maintain its catalytic activity. Water not only serves as a solvent, but also as a medium required for lipase activity, and also helps to separate lipase from the products after the reaction.

[0025] Furthermore, the preparation method of the hydrophobic dispersion described in S4 is: 5-20% calcium carbonate, 10-20% fly ash, 5-15% bentonite, 1-10% silicon dioxide and the remainder of fluorinated alkylsilane are ball-milled and mixed, and then water is added to obtain a hydrophobic dispersion with a concentration of fluorinated alkylsilane of 0.1-1wt%.

[0026] Description: Fluorinated alkyl silane has extremely strong hydrophobicity due to the presence of fluorine chains, which can significantly reduce the surface energy of non-woven fabrics and improve their water repellency; it works synergistically with calcium carbonate, fly ash, bentonite and silica to form a stable hydrophobic layer to ensure the performance of non-woven fabrics in high humidity or water contact environments; calcium carbonate and silica as fillers can enhance the physical strength and wear resistance of non-woven fabrics; the fine particles of fly ash can fill the micropores of non-woven fabrics to improve the density, and the glass phase components of fly ash help to form a more uniform hydrophobic layer; through ball milling mixing, the various components are evenly dispersed, and the formed hydrophobic dispersion can be more evenly covered on the surface of non-woven fabrics, optimizing the microporous structure and maintaining good air permeability; the adsorption of bentonite can absorb moisture and impurities, improve the chemical stability of non-woven fabrics, and extend the service life.

[0027] Further, in S4, the modified fibers obtained in S3 are divided into two groups according to a mass ratio of 1 to 4:1, respectively recorded as modified fiber a and modified fiber b, and the modified fiber a is immersed in a hydrophobic dispersion and stirred and immersed for 5 to 15 minutes, a hydrophobic treatment layer is attached to the surface of the modified fiber to form a layer, which is fished out and dried to obtain hydrophobic fibers; the modified fiber b is laid in a criss-cross manner using a multi-channel web laying machine, and the direction of each layer of fiber web is perpendicular to the previous layer, and the number of web laying layers is 6 to 20 layers. After all layers are laid, the fiber webs are bonded, and a part of the microporous structure is retained to control the porosity at 60 to 85%, and the non-woven fabric is heat-set at a temperature of 200°C and a time of 45 to 55 seconds to obtain a breathable layer; the hydrophobic fibers are evenly laid on the upper and lower surfaces of the breathable layer, and bonded to form a non-woven fabric with a microporous structure.

[0028] Description: The hydrophobic treatment of modified fiber a ensures that the surface of the non-woven fabric has excellent hydrophobic properties and effectively prevents water droplet penetration. The web laying and bonding of modified fiber b forms a breathable layer with high porosity to maintain good air permeability. Hydrophobic fibers are laid on the upper and lower surfaces of the breathable layer to form a hydrophobic, breathable and hydrophobic structure, which not only ensures that moisture cannot easily penetrate, but also maintains the air permeability of the non-woven fabric. Through web laying and bonding, the physical strength and stability of the non-woven fabric are improved, ensuring durability in a variety of application environments; the porosity design of 60-85% not only ensures air permeability, but also ensures the lightness and flexibility of the non-woven fabric.

[0029] Furthermore, the bonding method is hot pressing bonding, the hot pressing temperature is 170-240° C., the pressure is 1-3 MPa, and the compaction speed is 10-30 m / min.

[0030] Description: In the temperature range of 170-240℃, the hot melt adhesive or thermoplastic components in the fiber can be fully melted, and with a pressure of 1-3MPa, a strong bond between the fibers is ensured, thereby improving the tensile strength and durability of the non-woven fabric. A moderate compaction speed can ensure sufficient contact and bonding between the fibers, avoiding insufficient bonding due to too fast a speed, and prevent excessive compaction due to too slow a speed, thereby affecting air permeability. Reasonable settings of temperature and pressure can make the surface of the non-woven fabric smoother, the fiber distribution more even, improve the comfort of the hand, and improve the aesthetics of the finished product.

[0031] The beneficial effects of the present invention are as follows: the present invention can make the non-woven fabric maintain high air permeability while effectively blocking the invasion of water molecules due to its extremely low surface energy and hydrophobic properties; the addition of nano-silicon dioxide and polyurethane resin significantly improves the mechanical strength and durability of the non-woven fabric, so that it can withstand greater physical pressure and wear and tear while maintaining its lightweight characteristics; the addition of antistatic agent reduces the accumulation of static electricity generated by friction during the use of the material; polyester fiber, as the main component, provides the basic structure and cost advantages of the non-woven fabric, while ensuring the flexibility and certain elasticity of the material; the waterproof performance of the non-woven fabric is further enhanced by the hydrophobic treatment layer, and the hydrophobic treatment is performed before the filaments are bonded to make the fabric, which can enhance the hydrophobicity of the non-woven fabric without affecting the air permeability, so that high air permeability and waterproof performance coexist. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a bar graph of water vapor transmission rate test of samples of Examples 1 to 3, 16 to 19 of the present invention and Comparative Examples 1 to 3;

[0033] Figure 2 It is a bar graph of the water impermeability test of samples of Examples 1 to 3, 16 to 19 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0035] Embodiment 1: A highly breathable and hydrophobic nonwoven fabric, which is composed of 12.5% ​​PTFE powder, 7.5% nano-silicon dioxide, 4.5% polyurethane resin, 2% antistatic agent and the remainder polyester fiber extruded filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 45 mg / m 2 ;

[0036] The method for preparing the highly breathable and hydrophobic nonwoven fabric comprises the following steps:

[0037] S1. Raw material mixing

[0038] The polyester fiber, PTFE powder, nano-silicon dioxide, polyurethane resin and antistatic agent are uniformly mixed according to the formula ratio to obtain a mixture; the antistatic agent is antistatic agent ZJ-NW16; the cooling rate described in S3 is 6.5°C, and the stretching ratio is 1.75 times;

[0039] S2. Preparation of molten mixture

[0040] The mixed material obtained in S1 is introduced into a melt extruder, and the temperature is controlled to 240° C. to fully melt the PTFE powder to obtain a molten mixture;

[0041] S3, extrusion modification treatment

[0042] The molten mixture obtained in S2 is stretched into filaments through an electrospinning device, the filaments are cooled to room temperature, then immersed in deionized water for cleaning, and after drying, the filaments are completely immersed in a lipase solution and stirred for reaction for 9 hours; then the filaments are fully washed with distilled water and dried to obtain modified fibers; the temperature of the stirring reaction is controlled at 50° C.; the lipase solution is composed of 4.5% Novozym 435, 9% ethylene glycol and the remainder water by mass percentage;

[0043] S4. Preparation of non-woven fabric

[0044] The modified fiber obtained by S3 is divided into two groups according to a mass ratio of 5:2, and they are respectively recorded as modified fiber a and modified fiber b. The modified fiber a is immersed in a hydrophobic dispersion, stirred and immersed for 10 minutes, and a hydrophobic treatment layer is attached to the surface of the modified fiber, and then it is fished out and dried to obtain hydrophobic fiber; the modified fiber b is laid in a criss-cross manner by a multi-channel web laying machine, and the direction of each layer of fiber web is perpendicular to the previous layer. The number of web laying layers is 13 layers. After all layers are laid, the fiber webs are bonded, and a part of the microporous structure is retained to control the porosity at 72%. The non-woven fabric is heat-set at a temperature of 200°C and a time of 50s to obtain a breathable layer; the hydrophobic fibers are evenly laid on the upper and lower surfaces of the breathable layer, and a non-woven fabric with a microporous structure is made after bonding; the bonding method is hot pressing bonding, the hot pressing temperature is 205°C, the pressure is 2MPa, and the compaction speed is 20m / min;

[0045] The preparation method of the hydrophobic dispersion is as follows: 12.5% ​​calcium carbonate, 15% fly ash, 10% bentonite, 5% silicon dioxide and the remainder of fluorinated alkyl silane are ball-milled and mixed, and then water is added after being extracted to obtain a hydrophobic dispersion with a concentration of 0.5wt% of fluorinated alkyl silane;

[0046] S5. Finalization

[0047] The nonwoven fabric described in S4 is subjected to heat setting treatment, the temperature of the heat setting treatment is controlled to be 200° C., and the heat setting time is controlled to be 50 seconds, so as to obtain a highly breathable and hydrophobic nonwoven fabric.

[0048] Example 2: This example is basically the same as Example 1, except that, by mass percentage, it is composed of 10% PTFE powder, 5% nano-silicon dioxide, 3% polyurethane resin, 1% antistatic agent and the remainder polyester fiber extruded filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 10 mg / m 2 .

[0049] Example 3: This example is basically the same as Example 1, except that, by mass percentage, it is composed of 15% PTFE powder, 10% nano-silicon dioxide, 6% polyurethane resin, 3% antistatic agent and the remainder polyester fiber extruded filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 80 mg / m 2 .

[0050] Example 4: This example is basically the same as Example 1, except that the mixed material obtained in S1 is introduced into a melt extruder and the temperature is controlled to 220°C.

[0051] Example 5: This example is basically the same as Example 1, except that the mixed material obtained in S1 is introduced into a melt extruder and the temperature is controlled to 260°C.

[0052] Example 6: This example is basically the same as Example 1, except that the non-woven fabric described in S4 is subjected to heat setting treatment, the heat setting treatment temperature is controlled to be 180°C, and the heat setting time is 20s to obtain a highly breathable and hydrophobic non-woven fabric.

[0053] Example 7: This example is basically the same as Example 1, except that the non-woven fabric described in S4 is subjected to heat setting treatment, the heat setting treatment temperature is controlled to 220°C, and the heat setting time is 80s to obtain a highly breathable and hydrophobic non-woven fabric.

[0054] Example 8: This example is basically the same as Example 1, except that the cooling rate described in S3 is 3°C and the stretching ratio is 1.5 times.

[0055] Example 9: This example is basically the same as Example 1, except that the cooling rate described in S3 is 10°C and the stretching ratio is 2 times.

[0056] Example 10: This example is basically the same as Example 1, except that the temperature of the stirring reaction in S3 is controlled at 40°C.

[0057] Example 11: This example is basically the same as Example 1, except that the temperature of the stirring reaction in S3 is controlled at 60°C.

[0058] Example 12: This example is substantially the same as Example 1, except that, by mass percentage, the lipase solution in S3 consists of 0.1% Novozym 435, 3% ethylene glycol and the remainder water.

[0059] Example 13: This example is substantially the same as Example 1, except that, by mass percentage, the lipase solution in S3 consists of 9% Novozym 435, 15% ethylene glycol and the remainder water.

[0060] Example 14: This example is basically the same as Example 1, except that the preparation method of the hydrophobic dispersion described in S4 is: 5% calcium carbonate, 10% fly ash, 5% bentonite, 1% silicon dioxide and the remainder of fluorinated alkylsilane are ball-milled and mixed, and then water is added after extraction to obtain a hydrophobic dispersion with a concentration of 0.1wt% of fluorinated alkylsilane.

[0061] Example 15: This example is basically the same as Example 1, except that the preparation method of the hydrophobic dispersion described in S4 is: 20% calcium carbonate, 20% fly ash, 15% bentonite, 10% silicon dioxide and the remainder of fluorinated alkylsilane are ball-milled and mixed, and then water is added after extraction to obtain a hydrophobic dispersion with a concentration of 1wt% of fluorinated alkylsilane.

[0062] Example 16: This example is basically the same as Example 1, except that the modified fiber a is immersed in a hydrophobic dispersion and stirred for 5 minutes, a hydrophobic treatment layer is attached to the surface of the modified fiber, and the fiber is fished out and dried to obtain the hydrophobic fiber; the modified fiber b is laid and bonded to obtain a breathable layer with an average porosity of 60 to 62%, and the hydrophobic fibers are evenly laid on the upper and lower surfaces of the breathable layer, and bonded to form a non-woven fabric with a microporous structure.

[0063] Example 17: This example is basically the same as Example 1, except that the modified fiber a is immersed in a hydrophobic dispersion and stirred for 15 minutes, a hydrophobic treatment layer is attached to the surface of the modified fiber, and the fiber is fished out and dried to obtain the hydrophobic fiber; the modified fiber b is laid and bonded to obtain a breathable layer with an average porosity of 83 to 85%, and the hydrophobic fibers are evenly laid on the upper and lower surfaces of the breathable layer, and bonded to form a non-woven fabric with a microporous structure.

[0064] Example 18: This example is basically the same as Example 1, except that the bonding method is hot pressing bonding, the hot pressing temperature is 170°C, the pressure is 1 MPa, and the compaction speed is 10 m / min.

[0065] Example 19: This example is basically the same as Example 1, except that the bonding method is hot pressing bonding, the hot pressing temperature is 240°C, the pressure is 3MPa, and the compaction speed is 30m / min.

[0066] Comparative Example 1: With reference to Example 1, the filaments are composed of 20% PTFE powder, 15% nano-silicon dioxide, 8% polyurethane resin, 5% antistatic agent and the remainder polyester fiber extruded therefrom, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 8 mg / m 2 .

[0067] Comparative Example 2: Using Example 1 as a reference, the modified fiber was not treated by soaking in a hydrophobic dispersion and was directly hot-pressed to prepare a non-woven fabric.

[0068] Comparative Example 3: With reference to Example 1, when preparing the non-woven fabric, both the modified fiber a and the modified fiber b were immersed in a hydrophobic dispersion and then heat-pressed and bonded to form the non-woven fabric.

[0069] In order to explore the performance of nonwoven fabrics manufactured in Examples 1 to 3, 16 to 19 and Comparative Examples 1 to 3, the main materials were determined according to the experimental formula and 10 groups of samples were obtained for testing. Figure 1 , 2 The test results are as follows: Water impermeability adopts the test requirements specified in the JC / T2291 standard, water impermeability adopts the GB / T328.10 standard, and water vapor transmission adopts the GB / T17146 standard. The specific research is as follows: Water impermeability

[0070] 1. Explore the influence of the raw material ratio of highly breathable and hydrophobic non-woven fabrics on the performance of non-woven fabric samples:

[0071] like Figure 1 , 2 As shown, by comparing Examples 1 to 3, it can be seen that: Example 1 has the largest water vapor permeability, and as the raw material ratio changes, the water vapor barrier property of the non-woven fabric changes, and Example 3 has the lowest water vapor permeability; Example 1 has the highest water impermeability, and Example 3 has a higher water impermeability than Example 2. It can be seen that the raw material ratio of the highly breathable and hydrophobic non-woven fabric has a greater influence on the breathable and hydrophobic properties of the non-woven fabric sample.

[0072] By comparing Example 1 with Control Example 1, it can be seen that the water vapor permeability of Control Example 1 is significantly lower than that of Example 1, and the air permeability of the raw material ratio of Control Example 1 is poor. The formulation of Example 1 achieves a better balance between air permeability and water vapor barrier properties, and is suitable for applications that require both good air permeability and water vapor barrier properties.

[0073] 2. Investigate the influence of the preparation process parameters of non-woven fabrics on the performance of highly breathable and hydrophobic non-woven fabric samples:

[0074] like Figure 1 , 2 As shown, by comparing Examples 16 and 17, it can be seen that in terms of water vapor transmission, the value of Example 16 is 1658 g / m 2 ×24h, significantly higher than 1287g / m 2 ×24h, which means that the material formula of Example 16 allows more water vapor to pass through than Example 17; the water impermeability index shows that the value of Example 16 is 117cm H2O, which is much lower than 151cm H2O of Example 17, which shows that the material of Example 16 is weak in water resistance;

[0075] By comparing Examples 16 and 17 with Control Example 2, it can be seen that: in terms of water vapor transmission, Example 16 has the highest value, and the value of Control Example 2 is between Examples 16 and 17, and Example 16 is significantly higher than Control Example 2 in terms of water vapor transmission rate; the water impermeability index shows that the value of Control Example 2 is 102 cm H2O, which is lower than Examples 16 and 17, indicating that Control Example 2 has the weakest performance in terms of waterproofness.

[0076] 3. Investigate the influence of hot pressing bonding process parameters on the performance of highly breathable and hydrophobic non-woven fabric samples:

[0077] like Figure 1 , 2 As shown, Figure 1 , 2 As shown, by comparing Examples 18 and 19, it can be seen that the water vapor permeability of Example 18 is 1574 g / m 2 ×24h, compared with 1419g / m 2 ×24h is slightly higher, which shows that the process of Example 18 is better in terms of air permeability; the water impermeability index shows that the value of Example 18 is 132cm H2O, which is lower than 148cm H2O of Example 19, indicating that the material of Example 19 is better than Example 18 in terms of waterproof performance;

[0078] Comparing Examples 18 and 19 with Control Example 3, it can be seen that in terms of water vapor transmission, the values ​​of Examples 18 and 19 are both higher than 1286 g / m3 of Control Example 3. 2 ×24h, it can be seen that the air permeability of Control Example 3 is lower, and the water impermeability index shows that the value of Control Example 3 is 163cm H2O, which is higher than Examples 18 and 19, indicating that Control Example 3 has better waterproof performance.

Claims

1. A highly breathable and hydrophobic nonwoven fabric, characterized in that: The invention is composed of 10-15% PTFE powder, 5-10% nano-silicon dioxide, 3-6% polyurethane resin, 1-3% antistatic agent and the rest polyester fiber extruded filaments, and a hydrophobic treatment layer attached to the surface of the filaments; the mass coverage of the hydrophobic treatment layer on the surface of the filaments is 10-80 mg / m 2 .

2. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 1, characterized in that: The following steps are involved: S1. Raw material mixing The polyester fiber, PTFE powder, nano-silicon dioxide, polyurethane resin and antistatic agent are uniformly mixed according to the formula ratio to obtain a mixture; S2. Preparation of molten mixture The mixed material obtained in S1 is introduced into a melt extruder, and the temperature is controlled to be 220-260° C. to fully melt the PTFE powder to obtain a molten mixture; S3, extrusion modification treatment The molten mixture obtained in S2 is stretched into filaments through an electrospinning device, the filaments are cooled to room temperature, then immersed in deionized water for cleaning, and after drying, the filaments are completely immersed in a lipase solution and stirred for reaction for 3 to 15 hours; then, they are fully washed with distilled water and dried to obtain modified fibers; S4. Preparation of non-woven fabric The modified fiber obtained in S3 is immersed in a hydrophobic dispersion, stirred and immersed for 5 to 15 minutes, a hydrophobic treatment layer is attached to the surface of the modified fiber, and then taken out and dried to prepare a non-woven fabric with a microporous structure; S5. Finalization The non-woven fabric described in S4 is subjected to heat setting treatment, the temperature of the heat setting treatment is controlled to be 180-220° C., and the heat setting time is 20-80 seconds to obtain a highly breathable and hydrophobic non-woven fabric.

3. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 2, characterized in that: The antistatic agent described in S1 is antistatic agent ZJ-NW16.

4. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 2, characterized in that: The temperature of the stirring reaction in S3 is controlled at 40-60°C; the cooling rate is 3-10°C, and the stretching ratio is 1.5-2 times.

5. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 2, characterized in that: In terms of mass percentage, the lipase solution in S3 is composed of 0.1-9% Novozym 435, 3-15% ethylene glycol and the balance water.

6. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 2, characterized in that: The preparation method of the hydrophobic dispersion described in S4 is: by mass percentage, 5-20% of calcium carbonate, 10-20% of fly ash, 5-15% of bentonite, 1-10% of silicon dioxide and the remainder of fluorinated alkylsilane are ball-milled and mixed, and then water is added after extraction to obtain a hydrophobic dispersion with a concentration of fluorinated alkylsilane of 0.1-1wt%.

7. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 2, characterized in that: In S4, the modified fibers obtained in S3 are divided into two groups according to a mass ratio of 1 to 4:1, which are respectively recorded as modified fiber a and modified fiber b. The modified fiber a is immersed in a hydrophobic dispersion and stirred for 5 to 15 minutes. A hydrophobic treatment layer is attached to the surface of the modified fiber, which is fished out and dried to obtain hydrophobic fibers. The modified fiber b is laid in a criss-cross manner using a multi-channel web laying machine, and the direction of each layer of fiber web is perpendicular to the previous layer. The number of laying layers is 6 to 20. After all layers are laid, the fiber webs are bonded and a part of the microporous structure is retained to control the porosity at 60 to 85%. The non-woven fabric is subjected to heat setting treatment at a temperature of 200° C. and a heat setting time of 45 to 55 seconds to obtain a breathable layer. The hydrophobic fibers are evenly laid on the upper and lower surfaces of the breathable layer, and bonded to form a non-woven fabric with a microporous structure.

8. The method for producing a highly breathable and hydrophobic nonwoven fabric according to claim 7, characterized in that: The bonding method is hot pressing bonding, the hot pressing temperature is 170-240° C., the pressure is 1-3 MPa, and the compaction speed is 10-30 m / min.

Citation Information

Patent Citations

  • High-throughput efficient 2D net-shaped ultrafine nanofiber oil-water separation material and preparation method thereof

    CN107557894A

  • Preparation method of waterproof and breathable nanofiber membrane

    CN111719245A

  • Breathable fabric for protective clothing

    CN114889258A

  • Antistatic polyester fiber and preparation method thereof

    CN116516513A

  • Multilayer superfine nanofiber sterile barrier composite packaging material as well as preparation method and application thereof

    CN117984644A